A Study on Mobile banking Financial Transaction of Major Nationalized Banks in India - Krishna Prasad K.; P. Ushadevi, (International Journal of Management, Technology and Social Sciences (IJMTS), 2018)
Adopting new technology in the banking sector is very useful for the growth of banks in India. The bank is the main financial institution that provides the digital technology-enabled services to the customers in an effective manner. Because of competition today each and every bank is providing modern and innovative services to attract a number of customers. Mobile banking (also known as M-banking) is latest technology or novel technology, user-friendly, and widely used concept in Electronic banking that is used to accomplish cashless financial transactions, fund transfer, credit applications and payment of bills, taxes etc. remotely through mobile devices like smartphones, PDAs, and tablets. The uncommon increment in the utilization of mobile phones in both urban and rural areas provides exciting opportunities for the development of cell phone based banking. But in India, a developing country, mobile banking is limited to only some fields such as SMS due to lack of facilities, security issues, poorly performing internet connections and because of high priced. In this paper, we present a comparative study on Mobile Banking transaction of major banks in India. In this paper, we analyzed and discussed portable banking money/financial transactions, using ABCD analysis and based on the analysis we made a few proposals/recommendations to cell-phone enabled banking service contributor. This will encourage the scientist/researcher to find the gap between the traditional and digital method of financial transactions in India.